Deliberação, escolha, ação e responsabilidade moral em Aristóteles - Molon, Marcel André (My University, 2016)
Especially on EN III, Aristotle devoted himself to present the elements for a theory of action. Such a theory is detailed in the broad picture of what is meant by moral responsibility and requires an investigation of practical reasoning in human actions, which is effective at the deliberate choice. The action is always opened to the contraries and therefore undetermined, and will be voluntary if the principle is in the agent and the circumstances are known. However, not all voluntary action is deliberated, as in cases where the action is based on impulse or passion, but all deliberated choice is voluntary. Moreover, one question arises: where is it placed the moral responsibility itself? Would it be enough the willingness of the action or is it necessary deliberation and choice? This research seeks to understand these issues and the relation between the theory of action and virtue, in an attempt to better understand the elements that guide decision-making and, in particular, decision-making in the context of business management. Therefore, it is necessary to investigate the importance of the supreme human good, happiness, and the relevance of proper education of desires on the way of building the good habit and the conditions for perfect virtue. The path taken in this research includes the analysis of the motivation for actions and the justifications for each step in the evolution of the agent in its searching for perfect virtue, which will manifest itself in voluntary and deliberated chosen actions. In pursuit of the goals set for this thesis, one of the very important principles in Aristotle is in place: the constant attention of the accuracy and appropriate clarity in each investigation, according to the nature of the investigated object. Moral responsibility in Aristotle, it is possible to be identified in the combination of the actions taken by the character disposition of the agent, which includes not only the contingency and circumstance, but also a more profound subject, which is, precisely, the result of personal development of personal potentials, as a result of a lifetime of learning summed up.
Especialmente em EN III, Aristóteles dedicou-se a apresentar os elementos que compõem uma teoria da ação. Tal teoria se encontra detalhada no quadro amplo do que se entende por responsabilidade moral e requer a investigação do raciocínio prático implicado nas ações humanas, que é efetivado na escolha deliberada. A ação é sempre aberta aos contrários sendo, portanto, indeterminada, e será voluntária se o princípio motor estiver no agente e as circunstâncias forem conhecidas. Entretanto, nem toda ação voluntária é deliberada, como nos casos em que se age por ímpeto, de modo passional, mas toda escolha deliberada é voluntária. Mas, onde se situa, propriamente, a responsabilidade moral? Basta a voluntariedade da ação ou é necessário que haja deliberação e escolha? Esta pesquisa busca entender tais questões e a relação que há entre a teoria da ação e a virtude, em uma tentativa de melhor compreender os elementos que balizam a tomada de decisão e, em específico, a tomada de decisão no âmbito da gestão empresarial. Para tanto, há que se investigar a importância do bem humano supremo, a felicidade, além da importância da educação correta dos desejos na construção do bom hábito e na verificação das condições de construção da virtude perfeita. O caminho percorrido inclui a análise da motivação das ações e as justificativas para cada etapa na evolução do agente em busca da sua formação na direção da virtude perfeita, que se manifestará nas ações voluntárias, deliberadamente escolhidas. Na busca dos objetivos traçados para esta dissertação, esteve presente um dos preceitos de grande importância em Aristóteles: a atenção à precisão e clareza cabíveis em cada investigação, de acordo com a natureza do objeto investigado. A responsabilidade moral, em Aristóteles, é possível de ser identificada na conjugação das ações praticadas com a disposição de caráter do agente, o que inclui não só a contingência e a circunstância, mas também algo mais complexo, que é justamente o resultado do desenvolvimento pessoal dos potenciais humanos, fruto da soma do que foi apreendido pelo mesmo durante uma vida de aprendizado.
Keywords: Teoria da ação; Virtudes; Action theory; Virtues